The Effectiveness of YouTube Video Media in Social Studies Learning to Increase Student Learning Motivation - Irwansyah, Parulian; Widiastuti , Anik; Khotimah, Nurul; Safitri, Desy (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2025)
The Industrial Revolution 4.0 changed the paradigm to student-centered and accelerated the development of digital learning media. YouTube video media is a digital technology learning media that allows interesting, concrete, and contemporary social studies learning by Generation Z. The purpose of this study was to determine the effectiveness of YouTube video media in social studies learning to increase student learning motivation. The research methodology used a quasi-experimental approach with a pretest and posttest design. The population in this study amounted to 75 students from class VIII of SMP Negeri 2 Badau, Belitung District, Indonesia. Sampling was done by cluster random sampling. A total of 50 students were selected using cluster random sampling. The experimental group (n=25) was given YouTube video media learning, while the control group (n=25) was given conventional media in image media. The research instrument was a validated learning motivation questionnaire. Hypothesis testing was carried out using t-tests, while the increase in learning motivation used the N-gain test. The research findings showed an increase in student learning motivation. The experimental group showed a higher increase in learning motivation than the control group. This shows that YouTube video media in social studies learning effectively increases students' learning motivation. The implication of this research shows that YouTube video media has the potential to increase learning motivation in social studies learning. Further research on the effectiveness of YouTube video media can help social studies teachers use YouTube optimally to increase student learning motivation.